Comparative Analysis of Educational Development Strategies in Emerging Economies - Nugroho, Rizki (Advances: Jurnal Ekonomi & Bisnis, 2024)
Purpose: This study explores educational development strategies across emerging economies, examining how socio-economic, cultural, and political factors shape policy formulation and implementation. It aims to identify practical approaches for improving educational access and quality while addressing urban-rural disparities. Research Design and Methodology: A systematic literature review (SLR) synthesized peer-reviewed articles, government reports, and academic publications. The study compares strategies in developing countries, focusing on infrastructure development, curriculum reform, teacher training, and educational technology integration. Findings and Discussion: The findings reveal significant variations in strategies. Nigeria and Kenya prioritize rural infrastructure, while Vietnam and India emphasize curriculum reform and skill-based training. Although school participation rates have increased, challenges remain in achieving better learning outcomes. Educational technology has potential but faces limited internet access, insufficient teacher training, and low digital literacy in remote areas. Implications: The study highlights the need for adaptive, evidence-based policies tailored to local contexts. Policymakers should invest in teacher training, curriculum relevance, digital infrastructure, and community engagement. Future research should evaluate long-term policy impacts and explore innovative strategies to reduce educational disparities.